S54 Characterising sarcoidosis using a web-based registry: a pilot study. (16th November 2010) - Coker, R K; Wang, C; Sepahzad, A; Roberts, N J; Partridge, M R
Abstract : Introduction and Objectives: Sarcoidosis is a chronic multisystem disorder of unknown cause. Demographic and phenotypic characteristics have not been comprehensively studied in Britain. Extrapolation from a North American population (ACCESS) may not be valid. This retrospective pilot study aimed to evaluate the potential of a novel web-based registry, by recording demographic and clinical characteristics, follow-up and treatment. Methods: 199 potential patients were identified from specialist respiratory clinics at two hospitals. 135 case notes were reviewed. Data were extracted from first and follow-up visits with random data quality checks by at least one other author. Results: Of 135 patients, 55% were female and 47% Afro-Caribbean; mean age (years) was 43.7±12.3 and patients had on average three follow-up visits per year. Presenting symptoms included cough (95%), breathlessness (41%), skin rashes (22%), arthralgia (15%), fatigue (19%), eye symptoms (14%) and fever (11%). 14% had stage 0 chest radiographs, 46% stage I, 16% stage II, 15% stage III and 9% stage IV. 45% had raised serum angiotensin-converting enzyme at first visit. 80% had histological confirmation. Systemic corticosteroids were the commonest treatment (21.5% after first visit). Cutaneous involvement was highest in females (64%) and Afro-Caribbeans (48%). Nodular lesions were the most common; 77% had granulomas on skin biopsy. 94% of those with skin disease had other organ involvement and received on average three treatments (topical 77%, prednisolone 64%, and hydroxychloroquine 45%). During follow-up, 73% reported improvement. 20 patients had definite/probable neurosarcoid (Zajicek criteria). Symptoms included parasthesiae (45%), visual disturbance (30%), headache (30%), seizures (10%) and anosmia (5%). Four had a VIIth nerve palsy. Diagnosis was made on MRI in 95%; 20% had CNS biopsies. 80% received prednisolone and 25% intravenous methylprednisolone. 15% were discharged after remission. Of the rest, 40% deteriorated during follow-up, 40% stabilised and 20% improved. Raised serum ACE was common in those with cutaneous and neurological disease. Conclusions: A novel web-based registry is a valuable method of recording clinical data in sarcoidosis. Additional use by other centres and the prospective recording of details of new cases could provide useful epidemiological data for the UK and drive future hypothesis-based studies.